1976
DOI: 10.1093/ptj/56.4.414
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vestibular Stimulation on Nystagmus Response and Motor Performance in the Developmentally Delayed Infant

Abstract: The effects were studied of 10 days' exposure to daily repetitive, specific vestibular stimulation on motor performance of children with Down's syndrome and normal children. A quantitative assessment of vestibular function was made in these children including the habituation response of postrotatory nystagmus. Control groups were included. Both the children with Down's syndrome and the normal children who received vestibular therapy demonstrated positive effects when evaluated using a quantitative motor skills… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

1980
1980
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(30 citation statements)
references
References 0 publications
1
28
1
Order By: Relevance
“…Similarly, Chee, Kreutzberg, & Clark (1978) in a study of 23 preambulatory cerebral palsied children ages 2 -6 years reported that semi-circular canal stimulation over a four-week period resulted in improved reflexes and gross motor skills as compared to a similarly afflicted control group. Findings similar to these were reported by Kantner, Clark, Allen, & Chase (1976) in which a sample of Down's Syndrome children were given ten days' exposure to daily repetitive specific vestibular stimulation. The 10 days of vestibular stimulation resulted in a decline of vestibular induced postrotary nystagmus in Down's Syndrome and normal children, both also showing greater gains in tests of motor development than would be expected from age related norms.…”
Section: Perceptual-motor Training Intelligence and Academic Achievsupporting
confidence: 84%
“…Similarly, Chee, Kreutzberg, & Clark (1978) in a study of 23 preambulatory cerebral palsied children ages 2 -6 years reported that semi-circular canal stimulation over a four-week period resulted in improved reflexes and gross motor skills as compared to a similarly afflicted control group. Findings similar to these were reported by Kantner, Clark, Allen, & Chase (1976) in which a sample of Down's Syndrome children were given ten days' exposure to daily repetitive specific vestibular stimulation. The 10 days of vestibular stimulation resulted in a decline of vestibular induced postrotary nystagmus in Down's Syndrome and normal children, both also showing greater gains in tests of motor development than would be expected from age related norms.…”
Section: Perceptual-motor Training Intelligence and Academic Achievsupporting
confidence: 84%
“…Most important in the context of this review, repeated rotatory stimulation has shown to improve motor skills of young autistic infants (Kantner et al, 1976).…”
Section: Vestibular Stimulation In Neurodevelopmental Disordersmentioning
confidence: 97%
“…1O,25 This characteristic is documented to be evident in children with Down's syndrome. 26-28 Levitt,29 basing evidence of the efficacy of vestibular stimulation for this population on a study by Kantner et al,9 concluded that vestibular stimulation was useful in habituating the hyperexcitable vestibular system of children with Down's syndrome. The most recent authors advocating this treatment were Edwards and Yuen.…”
Section: Synaptic Modulationmentioning
confidence: 99%
“…In particular, researchers have attended only to the efficacy of vestibular-based interventions. [9][10][11][12] Vestibular stimulation in the context of sensory integration therapy A knowledge of the physiological and anatomical structure and function of the vestibular system is necessary as a basis for understanding the theory of sensory integrative functioning. In short, the vestibular apparatus is a receptor system comprised of three almost perpendicular semicircular canals and otolith organs (utricles and saccutes) located bilaterally in the bony canals of the inner ear.…”
Section: Introductionmentioning
confidence: 99%